Mechanical and Thermal Properties of Geopolymers from Mixtures of Coal Ash and Rice Hull Ash using Water Glass Solution as Activator - Kalaw, Martin Ernesto L.; Culaba, Alvin B; Nguyen, Hoc Thang; Nguyen, Khoi; Hinode, Hirofumi; Kurniawan, Winarto; Gallardo, Susan M; Promentilla, Michael Angelo B. (ASEAN Journal of Chemical Engineering, 2015)
Geopolymers, from industrial wastes such as blast furnace slag, red mud, and coal ash, among others, have emerged as technically viable, economically competitive, and environmentally attractive supplements and even alternatives to ordinary Portland cement (OPC). Furthermore, while the most impact shall be achieved with large-scale use in the general building and structural sector, as replacement or supplement to OPC, the properties of these geopolymers may be optimized for special niche applications. One of these applications is for light weight, low thermal conductivity, heat resistant, and moderate strength cement binder for low rise residential buildings. In this study, compressive strength, heat resistance, volumetric weight, mass loss, water absorption and thermal conductivity of geopolymers formed from mixtures of coal bottom ash and rice hull ash (CBA-RHA) and coal fly ash and rice hull ash (CFA-RHA) with sodium silicate solution (modulus 2.5) as activator were evaluated. Using mixture design and the JMP statistical software, the CBA-RHA combination at a mass ratio of 46% CBA, 32% RHA with 22% WGS gave properties at maximum desirability of 17.6 MPa compressive strength, 1640 kg/m3 volumetric weight, 273 kg/m3 water absorption, 28 MPa compressive strength after high temperature exposure (1000oC for 2 hours) with 4.4% mass loss, and 0.578 W/m-K thermal conductivity. On a performance basis, even as the geopolymers are formed as paste, these properties fall within the standards for lightweight OPC based-concrete with strength requirements for residential buildings. The low thermal conductivity and higher strength after high temperature exposure vis-à-vis OPC are additional advantages for consideration.